2015
DOI: 10.1111/vox.12275
|View full text |Cite
|
Sign up to set email alerts
|

An open, prospective trial investigating the pharmacokinetics and safety, and the tolerability of escalating infusion rates of a 10% human normal immunoglobulin for intravenous infusion (IVIg), BT090, in patients with primary immunodeficiency disease

Abstract: Shortening infusion time may reduce overall healthcare spending, for example nursing time needed, and also minimize disruption of patients' daily routine, especially for those patients in work or school settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The rate of infusions with potentially related AEs relative to the total number of infusions range from 4.1% (Gelfand and Hanna ) to 71.7% (Krivan et al. ), and the rate of patients experiencing at least 1 AE relative to the total number of patients range from 20.0% (Kallenberg ) to 87.1% (Robak et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rate of infusions with potentially related AEs relative to the total number of infusions range from 4.1% (Gelfand and Hanna ) to 71.7% (Krivan et al. ), and the rate of patients experiencing at least 1 AE relative to the total number of patients range from 20.0% (Kallenberg ) to 87.1% (Robak et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, it is important to consider that all children were included in the 10% product group, of which 46.2% experienced treatmentrelated AEs compared with 15.8% of adults in the same 10% group. Regrettably, when it came to the interpretation of the impact of age on infusion-related AEs in the 10% treatment group, it was difficult since the published studies reporting safety of 10% IVIG products in adults and children (whether in PID/SID [Church et al 2006;Gelfand and Hanna 2006;Stein et al 2009;Sleasman et al 2010;Wasserman et al 2012;Blazek et al 2015;Krivan et al 2015] or in autoimmune disease [Robak et al 2009;Blazek et al 2015]) do not assess their results according to patient's age. Clinical study population analyses reported in the literature have shown that children and elderly may be more susceptible to AEs of treatments in general (Woods et al 2005;Priyadharsini et al 2011;Alomar 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of any association may indicate that the sample size and power of this study may have been too small to detect the positive correlation between change in plasma concentration and Ig dose, which has been demonstrated in a number of contemporary studies . Ig studies are at particular risk of this due to the very high interindividual patient variability, which has been documented repeatedly .…”
Section: Patient Outcome – the Need For Empirical Datamentioning
confidence: 88%
“…2). It is unavoidable that patients will be under-or overdosed if a fixed weightbased dose is applied to Ig, which has such a large interpatient variability [14,52,56,57,63,69,70]. It is essential, therefore, that consideration is given to both clinical and laboratory outcomes to determine whether the delicate balance has been met.…”
Section: Implications For Clinical Practicementioning
confidence: 99%